Flow, compaction and tabletting properties of co-processed excipients using pregelatinized ofada rice starch and HPMC (2018)
The growing popularity of direct-compression process necessitates an ideal filler–binder that can substitute two or more excipients. Pregelatinization of starches significantly improves swelling and flow properties but produces tablets with low mechanical strength. When used as a binder in many tablet formulations, hydroxyl propyl methyl cellulose (HPMC) imparts mechanical strength but because of its poor flow during high speed tablet manufacturing, granulation of HPMC-based formulations is required prior to compaction. Directly-compressible co-processed excipients were developed utilizing pregelatinized starch of the indigenous Ofada rice starch (Oryza glaberrima Steud Family Poaceae) and HPMC. Co-processed excipients of various combinations of pregelatinized Ofada rice starch and HPMC K15M (15cps) were prepared using a co-fusion method (97.5:2.5; 95:5; 92.5:7.5; 90:10; 85:15; 80:20). The flow and compaction properties of the co-processed excipients, as well as, individual excipients were evaluated using density, Hausner ratio, Carr’s index, angle of repose, angle of internal friction, the Kawakita model, consolidation index and rate. Aceclofenac tablets were formulated using direct compression with starch, HPMC and specific co-processed excipients as filler-binders. Pregelatinization produced starch with larger granules and improved flow characteristics. FTIR spectra of the co-processed excipients confirmed absence of any chemical interaction. The angle of repose, Hausner ratio, Carr’s index, angle of internal friction indicated that flow properties improved with increasing starch content of the co-processed excipients. Kawakita plots, consolidation index and consolidation rate demonstrated cohesiveness while compressibility and rate of packing were enhanced. Aceclofenac tablets containing co-processed excipients exhibited a crushing strength ≥ 66.03 ± 1.58 MNm-2; friability ≤ 1%; disintegration time ≤ 10.75 ±3.10 minutes and dissolution time (t80) ≤ 30.00 ± 3.07 minutes. The co-processed excipients of pregelatinized Ofada rice starch and HPMC could be cheaper alternatives to other synthetic excipients used in direct compression of tablets assuming the starch would meet all compendial specifications.